2020
DOI: 10.9734/irjpac/2020/v21i1030210
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Concentrations and Source Characterization of Polycyclic Aromatic Hydrocarbons in Surface Waters of the Imiringi River System

Abstract: Ten water samples were collected along the Imiringi water channel, cutting across several sub-communities of the upstream to downstream sections of the river. All samples were collected in the month of August 2019, reflecting increased tidal movement of water and aggravated pollutants redistribution which is typical of the rainy season. Analysis was carried out using the HP 6890 Plus gas chromatograph – flame ionization detector (GC-FID). The rate of ionization of each PAH component was directly proportional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 27 publications
5
18
0
Order By: Relevance
“…In addition, the high level of HPAHs (Benzo(b)fluoranthene and Dibenz(a,h)anthracene) is solely an indication of biomass combustion (Figure 2). A spatial variability trend similar to the current study was reported for surface water samples collected from Imiringi River [21]. Also, due to oil bunkering activities along the Azuabie creek, the affected water ways recorded outlier concentrations of hydrocarbons (TPH and PAHs) as compared to control location.…”
Section: Statistical Data Analysis For the Identification Of Spatial supporting
confidence: 86%
See 3 more Smart Citations
“…In addition, the high level of HPAHs (Benzo(b)fluoranthene and Dibenz(a,h)anthracene) is solely an indication of biomass combustion (Figure 2). A spatial variability trend similar to the current study was reported for surface water samples collected from Imiringi River [21]. Also, due to oil bunkering activities along the Azuabie creek, the affected water ways recorded outlier concentrations of hydrocarbons (TPH and PAHs) as compared to control location.…”
Section: Statistical Data Analysis For the Identification Of Spatial supporting
confidence: 86%
“…Also, the Oswan-4 sample site depicted anthracene (0.30012 mg/L) with the highest concentration, while chrysene (0.00041 mg/L) reflected the least concentration. In the same vein, Aigberua [21] had recorded relatively higher concentrations of high molecular weight PAH fractions.…”
Section: Pah Distributionmentioning
confidence: 88%
See 2 more Smart Citations
“…Environmental monitoring of the PAH levels of the water, soil, and fish was done and PAH levels were determined using the gas chromatography/flame ionization detector (GC/FID) method as described by Aigberua. 22 PAHs diagnostic ratios were used as a tool for the identification of the emission sources of the PAHs in the different environmental media. [23][24][25] Water samples were collected from five points in each study community using previously cleaned 1-L capacity glass bottles.…”
Section: Methodsmentioning
confidence: 99%